Risk of Stevens-Johnson Syndrome with AEDs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
An international case-controlled study of medication use and the risk of Stevens-Johnson syndrome or toxic epidermal necrolysis is reported by the Groupe Epidemiologie LY Stevens Johnson (ELYS), Department of Dermatology, and Department of Public Health, Universite Paris XII, Creteil, France; and centers in Boston, US; Milan, Italy; Freiburg, Germany; Porto, Portugal; and Toronto, Canada.